Scientific Study of Dalhanokta Anguli Pramana (Measurement) with reference to Purusha Ura Vistaar (Male Chest Breadth) - Yawale, Roshani; M, Yusuf Sheikh; Gurmule, Rajni; Sharma, Gopal (International Journal of Ayurvedic Medicine, 2024)
In Ayurveda the word “Pramana” refers to measurement. Ayurveda classic have explained the normal measurements of Anga Pratyanga in terms of Ayama (length), Vistaar (breadth), Utsedha (height) and Parinaha (circumference) with the help of Swa-Anguli Pramana (measurement by own finger). In the ancient time length, breadth, and height of body’s parts measured by using the technique of Anguli Pramana in which measurements of parts of body have given in terms of Swa-Anguli. It can be the perfect parameter irrespective of age, sex, race and place etc. Principles of Ayurveda have given the individualistic approach rather than the generalized by providing the concept of Swa-Anguli Pramana. Acharyas said that before we start the treatment one should do the Ayu Pariksha (longativity of life) of that patient which is depends upon proper measurement of parts and sub parts of body along with Sara of body. Present study was taken to validate the Dalnhokta Anguli Pramana of Purusha Ura Vistaar (Male chest breadth) which was given as 24 Angula. The data of Purusha Ura Vistaar of 60 healthy volunteers was collected and statistically analyzed. As the very less work has been done the current study was conducted. Keywords: Anthropometry, Swa-Anguli Pramana (measurements by own finger), Measurements, Diameter, Ayam (length),